Status of Sedition Law in Indian Democratic Setup with Special Reference to Freedom of Speech and Expression - Nitesh Kumar Chaturvedi; Pankaj Kumar Rawat (AG Volumes, 2026)
The word ‘Sedition’ has been derived from the word ‘Seditio’, which is the composition of two words ‘sed’ and ‘itio’. Sedition is a conduct or speech, which incites people to rebel against the authority of a state or monarch. Democracy is based essentially on free debate and open discussion, for that is the only corrective of government action in a democratic setup. Freedom of speech and expression is the cornerstone of democratic governance and the democratic process cannot work properly without enjoying this freedom. Freedom of speech and expression creates a channel for open discourse on issues in democracies. The law of sedition has been weaponised by each and every Union and State government in the Indian federal structure. The intention behind the use of the sedition law has prima facie been to crush dissent of the people and criticism of Governments. Social activists, students, heads of various NGOs, opposition leaders and journalists have been the prime targets of the offensive crime of sedition. In this chapter, the authors have explored the role of right to freedom of speech and expression in democratic governance and the constitutional limitations cast on it. In this chapter the authors has examined the judgments related to law of sedition wherein the Apex Court decided the constitutionality of Section 124A, Indian Penal Code, 1860. Finally, the authors have analysed the provision related to the law of sedition under the New Bharatiya Nyaya Sanhita, 2023.